(untitled) (Research, Society and Development, 2020)
Objective: To develop a bundle-shaped Educational Technology on immunobiological conservation to assist continuing education practices in the vaccine room at the local level. Methodology: Methodological study, directed to the vaccine room of a School Health Center, located in Belém-PA, from September to November 2019. For the elaboration, a bibliographic survey on immunobiological conservation was carried out. Data analysis was performed from the grouping and organization of the information collected in an electronic spreadsheet structured in the Microsoft Excel program® 2010. Results: Based on the analysis, the themes to be highlighted in the bundle were defined, being: correct form of storage and administration of immunobiologicals; how to correctly perform the measurement of the temperature of the immunological; in addition to the contingency plan. Conclusion: Good practices in immunobiological storage are presented as ensuring the effectiveness of immunization.